Analysis of the microtensile bond strength to enamel of two adhesive systems polymerized by halogen light or LED Análise da microtração em esmalte de dois sistemas adesivos ativados por LED ou por luz halógena - Ana Paula Morales Cobra Carvalho; Míriam Lacalle Turbino (Sociedade Brasileira de Pesquisa Odontológica, 2005)
With the development of composite resin polymerization techniques, LEDs were introduced to the market place. Based on the studied literature, the aim of this study was to evaluate, through microtensile testing, the bond strength to enamel of a composite resin associated to a conventional (multi-bottle) adhesive system or to a self etching primer adhesive system, polymerized by halogen light or LED (light emitting diode). Bovine teeth were divided into 4 groups with 10 teeth each (n = 10). Then the adhesives Scotchbond Multipurpose Plus (3M-ESPE) and Clearfil SE Bond (Kuraray) were applied following the manufacturers' instructions. Both systems were polymerized for 10 s by halogen light (Degulux Soft Start - Degussa Hulls) set at 550 mW/cm² or by LED (Kerr Demetron) set at 600 mW/cm². The composite resin Filtek Z-250 was applied in four 1 mm increments with the aid of a square, condensation silicon, 5 mm x 5 mm matrix, and polymerized by either of light sources for 40 s. Scotchbond Multipurpose Plus polymerized by halogen light presented the highest bond strength values (39.69 ± 7.07 MPa), and the other groups did not present statistically significant differences: Scotchbond Multipurpose Plus polymerized by LED (22.28 ± 2.63 MPa), Clearfil SE Bond polymerized by halogen light (27.82 ± 2.65 MPa) and by LED (22.89 ± 5.09 MPa). Com a grande busca pelo desenvolvimento das técnicas de polimerização das resinas compostas e dos sistemas adesivos, foram introduzidos no mercado os LEDs. Com base na literatura estudada, neste trabalho é avaliada a força de união da resina composta ao esmalte associado a um sistema adesivo convencional e a um sistema autocondicionante polimerizados por luz halógena e LED, por meio do teste de microtração. Os dentes bovinos foram divididos em 4 grupos com 10 dentes em cada um (n = 10), para aplicação do adesivo Scotchbond Multipurpose Plus (3M-ESPE) e do Clearfil SE Bond (Kuraray) conforme orientação do fabricante, ambos polimerizados por 10 s tanto pela luz halógena (Degulux Soft Start - Degussa Hulls) com potência de 550 mW/cm² como pelo LED (Kerr Demetron) com potência de 600 mW/cm². A resina composta Filtek Z-250 foi aplicada em 4 incrementos de 1 mm com auxílio de uma matriz de silicona de condensação de formato quadrado com dimensões de 5 mm x 5 mm; sendo polimerizada tanto pela luz halógena como pelo LED por 40 s. O adesivo Scotchbond Multipurpose Plus polimerizado com luz halógena apresentou os maiores valores de adesão (39,69 ± 7,07 MPa) e os outros grupos não apresentaram diferença estatisticamente significante entre si: Scotchbond Multipurpose Plus polimerizado por LED (22,28 ± 2,63 MPa), Clearfil SE Bond polimerizado por luz halógena (27,82 ± 2,65 MPa) e por LED (22,89 ± 5,09 MPa).